Emphysematous Aortitis due to Clostridium septicum in an 89-Year-Old Female with Ileus - Susana Urgiles; Harold Matos-Casano; Kyaw Zin Win; Jeronimo Berardo; Utpal Bhatt; Jilan Shah (Case Reports in Infectious Diseases)
Emphysematous aortitis is a rare but lethal form of infectious vasculitis. This condition was found incidentally on computed tomography of the chest during the evaluation of a patient presenting with pneumonia coincident with adynamic ileus. The patient did not have a history of malignancy. While colon cancer could not be ruled out, it is possible that ileus may have contributed to or resulted in bacterial translocation in this case. Appropriate investigations and empirical therapy against Clostridium septicum should be initiated in the presence of clinical and radiological findings suggestive of emphysematous aortitis.